Stephania polygona (Menispermaceae), a new species from Southern Vietnam - Chinh, Vu Tien; Van, Duy Nong; Tran, van Tien; Xia, Nianhe (Phytotaxa, 2019)
A new species, Stephania polygona N.H. Xia & V.T. Chinh, is described and illustrated from southern Vietnam. It is similar to S. subpeltata and S. elegans in general appearance, but differs by its polygonous lobed leaf blade, five to eight veins, and longer, red purple sepals.